PENGARUH LITERASI EKONOMI DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI TULUNGAGUNG TAHUN AKADEMIK 2019/2020 - Lailina Agustin; Sulastri Rini Rindrayani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2021)
Abstract : Consumptive behavior is the behavior of someone who consumes and possesses goods that are less needed just to fulfill the desires of pleasure and desire only to achieve maximum satisfaction. The problem in this study based on preliminary research shows that consumer behavior in online shopping is quite high. The purpose of this study was to determine: (1) the effect of economic literacy on consumer behavior of the University of Bhinneka PGRI Tulungagung University Economic Education Study Program 2019/2020 (2) the effect of self-control on the consumer behavior of the University of Bhinneka PGRI Tulungagung University Academic Education Study Program 2019/2020 (3) the effect of economic literacy and self-control on the consumptive behavior of the University of Bhinneka PGRI Tulungagung University Economic Education Study Program 2019/2020 academic. year. The research method uses quantitative research. The population in this study is all students of the Economic Education study program at Bhinneka University PGRI Tulungagung academic year 2019/2020 a number of 356 students. The number of samples in this study were 78 students. The research instrument in the study was using a questionnaire method. Assessment scores use a Likert scale. The data analysis method used is multiple linear regression analysis. The results of research shows that in partial of economic literacy (X1) has no effect on consumptive behavior (Y). While the self control influential on the consumptive behavior (Y). It was significant influence negative and between economic literacy and self control to the consumptive behavior of 41,8%. This research is expected that students can reduce their consumptive behavior.